A Ferrocene-Modified Carbon Electrode Prepared from Coconut Shell Char for Cu(II) Detection in Water - Aulia, Nabila Putri; Rahmawati, Fitria; Masykur, Abu; Heraldy, Eddy (Makara Journal of Science, 2026)
A ferrocene (Fc)-modified carbon electrode was prepared from coconut shell char (CSC), which was activated with NaOH to produce an activated coconut shell carbon (Ac-CSC). The carbon electrode was designed as a printed-carbon electrode consisting of working, counter and reference electrodes in a single piece, called a screen-printed carbon electrode, or SPCE. An Fc solution was applied to the working electrode part at 10%, 20% and 30% mass of the SPCE, producing an SPCE-Fc as an electrochemical sensor for Copper ions Cu(II) detection. The prepared activated carbon was analysed by XRD, FTIR, SEM/EDX, surface area analysis and impedance measurement to determine its diffraction pattern, available specific functional groups, morphology, elemental content, surface area and electrical conductivity. The results showed that CSC consists of 52.89% amorphous carbon, 19.65% nitrogen and 23.12% oxygen. FTIR analysis showed C=O, C=C, C-H, C-O, O-H, N-H and C-S vibrations. The Ac-CSC provided an electrical conductivity rate of 26.025 S/cm. Cyclic voltammetry analysis of the Cu(II) solution with SPCE-Fc10% provided the highest current density among the other Fc contents. Therefore, a further study used SPCE-Fc10% to determine the limit of detection (LoD), interference effects, pH and scan rate effects, the repeatability of the analysis and the reproducibility of SPCE-Fc10% for Cu(II) detection. The LoD was 0.055 mM. The electrode fabrication also showed good reproducibility, as evidenced by a repeatability coefficient (R) of 0.06. The interference test showed that the SPCE-Fc10% selectively detected Cu(II), even in the presence of 5% volume of Pb(II) and Co(II) in the Cu(II) solution.